The Lega Nord and the Politics of Secession in Italy - Bull, A. author. aut Link
IX, 204 p.
Keywords: Since the late 1980s, the Lega Nord has broken the mould of Italian politics. Federalist, secessionist, populist, it has succeeded in mobilizing the entrepreneurial class of Northern Italy in a campaign against the Italian state. In 1996, it launched the idea of Panadia, a separate Northern Italian nation. This proved to be a step too far, but the Lega remains a political force to be reckoned with, and has propelled 'the Northern question' on to the national stage.